El Excentrico, 1979-05-20 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
May 20, 1979 [20 de mayo de 1979]. Ano 30, No 4. Cover contains a photo of Bert Garcia and his two sons at the Cinco de Mayo Parade. The headline reads, "Cinco de Mayo Parade: La Familia Garcia" (transl: The Family Garcia).